Quantitation of paracetamol by liquid chromatography-mass spectrometry in human plasma in support of clinical trial - Plewes, K; Tarning, JO; Dondorp, AM; Ghose, A; Wong, HT; Kam, RK; Chan, MH (Future Science, 2018)
Background: Paracetamol is a well-tolerated antipyretic widely used in severe malaria management. The study aimed to develop and validate a rapid liquid chromatography mass spectrometry (LC-MS/MS) assay to quantify paracetamol in plasma from patients with severe malaria. Results: Plasma samples were extracted with organic solvent and assayed in less than 5.5 minutes. The assay response was linear (0.125-50 mg/L) with total intra- and inter-assay imprecision of <1.4%, which were considerably lower than most published reports. Conclusions: We developed, validated and applied a rapid, and small volume LC-MS/MS assay with high precision and accuracy for plasma paracetamol quantitation in 989 samples from 62 patients with severe malaria. The simple and high-throughput quality could facilitate assay automation for future clinical studies.